Essays presented to Michael Hicks - Clark, Linda, 1946-; Hicks, Michael, 1948- (Fifteenth century, 2015)
For four decades, Michael Hicks has been a figure central to the study of fifteenth-century England. His scholarly output is remarkable both for its sheer bulk and for the diversity of the fields it covers. This extraordinary breadth is reflected by the variety of subjects covered by the papers in the present volume, offered to Professor Hicks by friends, colleagues and former students to mark his retirement from the University of Winchester. Fifteenth-century royalty, nobility and gentry, long at the heart of his own work, naturally take centre stage, but his contribution to economic and regional history, both in the early part of his career as a research fellow at the Victoria County History and more recently as director of a succession of major research projects, is also reflected in the essays presented here.0.